The metal transporter SMF‐3/DMT‐1 mediates aluminum‐induced dopamine neuron degeneration. (21st November 2012) - VanDuyn, Natalia; Settivari, Raja; LeVora, Jennifer; Zhou, Shaoyu; Unrine, Jason; Nass, Richard
Abstract Aluminum (Al3+) is the most prevalent metal in the earth's crust and is a known human neurotoxicant. Al3+ has been shown to accumulate in the substantia nigra of patients with Parkinson's disease (PD), and epidemiological studies suggest correlations between Al3+ exposure and the propensity to develop both PD and the amyloid plaque‐associated disorder Alzheimer's disease (AD). Although Al3+ exposures have been associated with the development of the most common neurodegenerative disorders, the molecular mechanism involved in Al3+ transport in neurons and subsequent cellular death has remained elusive. In this study, we show that a brief exposure to Al3+ decreases mitochondrial membrane potential and cellular ATP levels, and confers dopamine (DA) neuron degeneration in the genetically tractable nematode Caenorhabditis elegans (C. elegans). Al3+ exposure also exacerbates DA neuronal death conferred by the human PD‐associated protein α‐synuclein. DA neurodegeneration is dependent on SMF‐3, a homologue to the human divalent metal transporter (DMT‐1), as a functional null mutation partially inhibits the cell death. We also show that SMF‐3 is expressed in DA neurons, Al3+ exposure results in a significant decrease in protein levels, and the neurodegeneration is partially dependent on the PD‐associated transcription factor Nrf2/SKN‐1 and caspase Apaf1/CED‐4. Furthermore, we provide evidence that the deletion of SMF‐3 confers Al3+ resistance due to sequestration of Al3+ into an intracellular compartment. This study describes a novel model for Al3+‐induced DA neurodegeneration and provides the first molecular evidence of an animal Al3+ transporter.